2009
DOI: 10.1002/path.2667
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of interleukin‐17 family cytokines in intact and complicated human atherosclerotic plaques

Abstract: In addition to the classical TH1 and TH2 cytokines, members of the recently identified IL-17 cytokine family play an important role in regulating cellular and humoral immune responses. At present nothing is known about the role of these cytokines in atherosclerosis. Expression of IL-17A, -E and -F was investigated in atherosclerotic tissue by rtPCR and immunohistochemistry. IL-17E and its receptor were further studied in cultured smooth muscle cells and endothelial cells, using rtPCR and western blot. rtPCR sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
131
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 35 publications
(42 reference statements)
6
131
0
6
Order By: Relevance
“…First, as in previous studies (18,43,44), we used a polyclonal goat antibody to IL-17A that can also cross-react, to a certain degree, with IL-17F. Even though the ELISA used for the ex vivo biopsy experiments was specific for IL-17A, and previous in vitro experiments have demonstrated the production of IL-17A by human mast cells (18), it still remains to be formally demonstrated which IL-17 isotype is produced by mast cells in the synovial tissue.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…First, as in previous studies (18,43,44), we used a polyclonal goat antibody to IL-17A that can also cross-react, to a certain degree, with IL-17F. Even though the ELISA used for the ex vivo biopsy experiments was specific for IL-17A, and previous in vitro experiments have demonstrated the production of IL-17A by human mast cells (18), it still remains to be formally demonstrated which IL-17 isotype is produced by mast cells in the synovial tissue.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the production and secretion of cytokines are regulated in a manner different from the degranulation function (40)(41)(42). Based on the recent description of IL-17 production by mast cells in inflammatory diseases (19,43,44) and considering the emerging role of IL-17 in SpA (30), we focused on the expression and production of IL-17 by mast cells in SpA synovitis. Our results confirmed not only that synovial mast cells express IL-17, but also that both the absolute number of mast cells and the proportion of synovial mast cells expressing IL-17 is significantly increased in SpA synovitis when compared to RA synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of this event could be now evaluated in diseases where MCs represent a potent source of proinflammatory cytokines and exposure to AhR ligands is likely to occur (38). For instance, MCs alone or together with other non-T immune cells are predominant IL-17 + cells in psoriatic lesions in human skin (25), in atherosclerotic plaques (39), as well as in rheumatoid arthritis, osteoarthritis, and spondyloarthritis synovium (24,26,40). Human MCs require the Th17 lineage-defining transcription factor Rorc to produce IL-17 in response to different stimuli (24).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IL-17A in cells of the granulopoietic pathway has not been reported in human cancers, although such cells were found in human atheromatous plaques. 7 It has been reported that myeloid-derived suppressor cells can express IL-17 and promote tumor development in a murine hepatocarcinoma model. 39 Because all CLL spleens had higher numbers of immature myeloid cells than spleens from healthy individuals, a previously unrecognized splenic granulopoiesis may occur in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…6 IL-17 is produced by Th17 cells and other cells: CD8 + T cells, γδ T cells, invariant NKT cells, mast cells, and granulocytes. 7 IL-17 has pleiotropic functions and multiple targets, mostly explored in mouse models and increasingly linked to human diseases. [8][9][10][11] Generation of human Th17 cells from naïve precursors is co-promoted by IL-6 and IL-1β and expansion of human Th17 cells is maintained by IL-23; 9 a role for transforming growth factor-β (TGF β) in human Th17-cell differentiation is controversial.…”
Section: Introductionmentioning
confidence: 99%